IMPLEMENTATION OF PT VALE INDONESIA TBK CSR IN THE COMMUNITY DEVELOPMENT AND EMPOWERMENT PROGRAM BASED ON THE INDEPENDENT RURAL AREA DEVELOPMENT PROGRAM IN SOROWAKO, NUHA DISTRICT - Khaliq Aisya Fatimah; Herlina Sakawati; Andi Aslinda (Universitas Negeri Makassar, 2026)
This study examines the implementation of PT Vale Indonesia Tbk’s corporate social responsibility (CSR) initiatives within the Community Development and Empowerment Program (PPM) based on the Independent Rural Area Development Program (PKPM) in Sorowako District and Nuha District. Data collection methods included observation, interviews, and documentation. Data analysis techniques included data reduction, presentation, and drawing conclusions. Vale Indonesia Tbk provides resources to support social responsibility programs focused on education, health, the economy, and social welfare. Vale Indonesia Tbk’s PPM-PKPM program aims to improve community welfare through enhancements in the economic, social, health, and educational sectors. As part of its corporate social responsibility, Vale Indonesia is the subject of this study. Research data was collected from January to May 2024. Data collection techniques included observation, interviews, and documentation. Data analysis techniques included data reduction, presentation, and drawing conclusions. Vale Indonesia Tbk provides resources to support corporate social responsibility programs focused on education, health, the economy, and social issues. The PPM-PKPM program of Vale Indonesia Tbk aims to improve community welfare by enhancing the economic, social, health, and educational sectors. As part of its corporate social responsibility, PT. Vale Indonesia Tbk has integrated social responsibility into its organizational structure.